Improving physical properties of Ultisol and maize yield using coconut shell biochar and Leucaena compost - Endriani; Listyarini, Diah; Farni, Yulfita (Brawijaya University, 2025)
Ultisol is generally characterized by a high clay content in the argillic horizon, easy compaction, slow permeability, and unstable aggregates, resulting in low total porosity. Organic soil amendments such as compost and biochar can be used to improve soil organic matter, aggregate stability, and other physical properties of Ultisol. A field experiment was conducted using a randomized block design to assess the potential effects of Leucaena compost (LC) and coconut shell biochar (CB) on the physical properties of Ultisol and maize yield. The treatments included combinations of compost (0, 5, and 10 t/ha), biochar (0, 5, and 10 t/ha), and inorganic fertilizer (50% and 100% of the recommended dose). The results showed that the application of Leucaena compost and coconut shell biochar improved the physical properties of the soil. Compost and/or biochar applications at 10 t/ha enhanced soil organic matter, total porosity, aggregate formation, aggregate stability, pore size distribution, and reduced soil bulk density, improving maize growth and yield.